Potential inhibitors of angiotensin converting enzyme 2 receptor of COVID-19 by Corchorus olitorius Linn using docking, molecular dynamics, conceptual DFT investigation and pharmacophore mapping. Issue 16 (2nd November 2022) - Mesli, Fouzia; Ghalem, Meriem; Daoud, Ismail; Ghalem, Said
Abstract: A novel coronavirus, previously designated 2019-nCoV, was identified as the cause of a cluster of pneumonia cases in Wuhan, a city in the Hubei Province of China, at the end of 2019. Our objective focuses on the in silico study to screen for an alternative drug that can block the activity of the angiotensin converting enzyme 2 (ACE2), which is a key protein in the physiology of Covid-19, necessary for the entry of the SARS-Cov-2 virus into the host's cells using natural compounds especially phenolic antioxidants, polyphenolics and pharmaceutically phytochemicals derived from the leaves of Corchorus olitorius Linn, appear to be very potential in controlling virus-induced infection. The results of the docking simulation revealed that méthyl-1, 4, 5-tri-O-caféoyl quinate has a stronger bond, high affinity and gives the best docking scores compared to, the co-crystallized inhibitor (PRD_002214) of the enzyme ACE2, chloroquine, hydroxychloroquine, captopril and simerprevir antiviral drugs. The ADMET properties, Pharmacokinetics and Medicinal Chemistry & P450 site of metabolism prediction, pharmacophore Mapper enzyme revealed that the compound méthyl-1, 4, 5-tri-O-caféoyl quinate generates a hypothesis which can be applied successfully in biological screening for further experiments. The novel MD computational technique study showed better conformational movements result for the méthyl-1, 4, 5-tri-O-caféoyl quinate-ACE2 docked complex. Therefore méthyl-1, 4, 5-tri-O-caféoyl quinate may be considered to be potential inhibitor of the main protease enzyme of virus, but need to be investigated in vivo and in vitro for further drug development process. Communicated by Ramaswamy H. Sarma